Epidemiology of Alternaria linicola on linseed (Linum usitatissimum L.) - Vloutoglou, Irene (1994)
Conidia of A. linicola germinated over a wide range of temperatures (5 - 25°C) on both agar and leaves. Germination started within 2 h after inoculation at temperatures between 10°C and 25°C, either on agar or on leaves. At 5°C, there were lag periods of 2 and 4 h before the initiation of germination on agar and on leaves, respectively. Germinating A. linicola conidia were very sensitive to drying between 2 and 6 h after inoculation. In the presence of leaf wetness, light applied before the initiation of germination delayed the germination process and decreased the length of the germ tubes. Light applied after the onset of germination decreased both the percentage of conidia which germinated and the length of the germ tubes. In the absence of leaf wetness, light applied before or after the initiation of germination stopped the germination process or decreased the percentage of conidia which germinated, respectively. Conidia of A. Linicola germinated by producing germ tubes and occasionally by producing secondary conidia. Formation of appressoria was inhibited at 5°C. Penetration of the leaf tissues started 12 h after inoculation at 15°C and occurred mainly directly through the epidermal cells and occasionally through stomata.